L’approche belge de la responsabilité environnementale dans le milieu marin : état des lieux - Hendrik Schoukens (VertigO)
Despite practice and (still) absent case law the Belgian Law of 20 January 1999 has introduced a completely innovative system, which may serve as an important legal lever for integrated management of the Belgian coastal area. By introducing no-fault liability, chapter X of the Law extends the possibilities of obtaining compensation for damage caused by marine pollution and will furthermore dissuade potential perpetrators from adopting harmful behaviour. The notion of environmental disturbance is particularly innovative by including damage to res communis and res nullius that do not belong to anyone, such as birds, fish and other marine animals. However, oil pollution, which is the principal source of pollution, falls in principle outside the scope of application of the civil liability regime. Moreover, by combining the principles of civil liability with the administrative system of prevention (implementing the Directive on environmental liability), the legislator has created certain ambiguities. The legislator will have the opportunity to clarify the uncertainties and ambiguities that are still present in the Law with the implementation of the Marine Strategy Framework Directive. In addition, this Directive will provide new tools that may help to clarify the notion of environmental disturbance and, if need be, the compensation measures more objectively. Integrated management of the coastal area may take a new step forward with the entry into force of this Directive.